Entourage : a tracing file and color sourcebook / Ernest Burden - Burden, Ernest1934-
The definitive tracing file for design professionals--updated and expanded--with color DVD. Packed with over 1500 traceable line drawings and more than 1300 color photographic images on the enclosed DVD, Entourage, Fifth Edition, provides a quick and easy way to create visually persuasive architectural presentations. This fully revised volume offers a vast assortment of contemporary entourage people, vehicles, trees and plants that helps architects, commercial artists, interior and graphic designers, and draftspersons bring designs to life. You'll also get tips for creating your own entourage file of images--including where to search, how to photograph them, and how to develop them into professional looking illustrations. Add more power and impact to your visual presentations using this invaluable, state-of-the-art resource.